2022
DOI: 10.3389/fimmu.2022.889138
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-mRNA Booster Vaccination Reverses Non-Responsiveness and Early Antibody Waning in Immunocompromised Patients – A Phase Four Study Comparing Immune Responses in Patients With Solid Cancers, Multiple Myeloma and Inflammatory Bowel Disease

Abstract: BackgroundIndividuals with secondary immunodeficiencies belong to the most vulnerable groups to succumb to COVID-19 and thus are prioritized for SARS-CoV-2 vaccination. However, knowledge about the persistence and anamnestic responses following SARS-CoV-2-mRNA vaccinations is limited in these patients.MethodsIn a prospective, open-label, phase four trial we analyzed S1-specific IgG, neutralizing antibodies and cytokine responses in previously non-infected patients with cancer or autoimmune disease during prima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 42 publications
6
50
0
Order By: Relevance
“…First, we demonstrated that anti‐TNF treatment attenuates the anti‐spike IgG concentration following third dose vaccination, compared to treatment with non‐anti‐TNF biologics and healthy controls, respectively (Figure 2A,B). These observations are in line with findings from CLARITY‐IBD, VIP, PREVENT‐COVID, HERCULES and Wagner et al, while the STOP COVID‐19 in IBD study could not find reduced antibody concentrations in anti‐TNF‐treated IBD patients when comparing them to IBD patients without immunosuppressive treatment 24–26,28–30 . Importantly, it must be noted that the reduced antibody responses found in this study, might at least partially be influenced by already reduced antibody concentrations in anti‐TNF‐treated patients after two vaccine doses as shown before 10–12,31–37 …”
Section: Discussionsupporting
confidence: 92%
“…First, we demonstrated that anti‐TNF treatment attenuates the anti‐spike IgG concentration following third dose vaccination, compared to treatment with non‐anti‐TNF biologics and healthy controls, respectively (Figure 2A,B). These observations are in line with findings from CLARITY‐IBD, VIP, PREVENT‐COVID, HERCULES and Wagner et al, while the STOP COVID‐19 in IBD study could not find reduced antibody concentrations in anti‐TNF‐treated IBD patients when comparing them to IBD patients without immunosuppressive treatment 24–26,28–30 . Importantly, it must be noted that the reduced antibody responses found in this study, might at least partially be influenced by already reduced antibody concentrations in anti‐TNF‐treated patients after two vaccine doses as shown before 10–12,31–37 …”
Section: Discussionsupporting
confidence: 92%
“…higher binding and neutralizing antibody titers to the WT and omicron variant after booster, however 5-7x decrease in both after 2-4 months post booster Wagner A, et al Front Immunol. ( 44 ) BNT162b2, mRNA1273 4 weeks yes yes no 63 (breast or lung cancer) 49 (78%) under active treatment 0 66 Sign. higher antibody levels and neutralizing capacity after booster Zeng C, et al Cancer Cell.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these data further show that antibody testing is generally not needed to confirm seroconversion and vaccine responsiveness after primary COVID-19 vaccination in healthy individuals. However, in individuals under immunosuppressive therapies antibody testing is useful to identify vaccine non-responders [ 15 , 16 ] and guide further prophylactic treatment options such as application of monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%